Local Annealing of Cold Rolled Aluminum Sheets by LASER Treatment - Bubonyi, Tamás; Bánóczy, Zsuzsanna; Barkóczy, Péter; Buza, Gábor (International Journal of Engineering and Management Sciences, 2019)
LASER treatment widely used in material processing technologies. The annealing is not the typical application of the LASER treatment, but this is possible to apply in case of cold deformed metals. In the article a cold rolled EN AW 8006 aluminum sheet is annealed by LASER treatment. The microstructure of the annealed sheets is observed by optical microscopy. An existing cellular automata simulation of recrystallization process is modified to study the LASER annealing. The observed microstructure and the simulated results are compared to determine the further development of the developed automaton.